Resilience and adaptive strategies for managing stigma in Chinese people with chronic kidney disease - Wei Xiong; Tianhui An (Scientific Reports)
Abstract Chronic kidney disease (CKD) is a significant global public health issue, with a substantial population in China. Influenced by traditional Chinese medicine that links kidney health to sexual vitality, people with CKD in China face unique societal stigmatization. This study aimed to explore the stigmatization experiences of individuals with CKD in China and their corresponding coping strategies. Employing a focused ethnographic approach, this research utilized participant observation within three WeChat groups and conducted offline semi-structured interviews with 30 individuals. The analysis of interviews and field transcripts reveals that people with CKD in China adopt a dualistic coping strategy metaphorically described as “huddling for warmth”: they externally conceal their condition to avoid social stigma while internally cultivating a strong communal identity through online and offline interactions. Despite the prevalent stigma, these individuals demonstrate remarkable resilience and agency through their proactive coping mechanisms. This study highlights the urgent need for the Chinese government, medical institutions, and the public to address this deep-rooted stigma and foster a more inclusive and supportive environment to enhance the well-being of people living with CKD.